2019
DOI: 10.1097/md.0000000000015414
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-fetoprotein to transaminase ratio is related to higher diagnostic efficacy for hepatocellular carcinoma

Abstract: Alpha-fetoprotein (AFP), as the most widely used biomarker of hepatocellular carcinoma (HCC), was correlated with ongoing liver damage. The aim of this study was to evaluate the ability of inflammatory correction-based AFP to identify HCC from other liver diseases.From March 2012 to March 2017, among 926 participants, a total of 501 patients whose transaminases were higher than the upper limit of normal range, including 166 treatment-naïve HCC patients were enrolled in our retrospective study. The liver functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
(24 reference statements)
1
10
0
Order By: Relevance
“…In the present study, we also compared the diagnostic value of AFP marker and AFP/(ALT × AST) ratio in diagnosing HCC. Liu X. et al rst used this novel index AFP/(ALT × AST) ratio in their study and found that the diagnostic value of AFP/(ALT × AST) ratio was signi cantly better than that of AFP, with AUC up to 0.853 (95% CI 0.818-0.887) and 0.825 (95% CI 0.782-0.868) for differentiating HCC from non-HCC patients and from cirrhosis patients, respectively [19]. Our current data also illustrated that the diagnostic value of the index AFP/(ALT × AST) ratio was superior to that of serum AFP marker for detecting HCC, especially in patients with elevated serum ALT level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we also compared the diagnostic value of AFP marker and AFP/(ALT × AST) ratio in diagnosing HCC. Liu X. et al rst used this novel index AFP/(ALT × AST) ratio in their study and found that the diagnostic value of AFP/(ALT × AST) ratio was signi cantly better than that of AFP, with AUC up to 0.853 (95% CI 0.818-0.887) and 0.825 (95% CI 0.782-0.868) for differentiating HCC from non-HCC patients and from cirrhosis patients, respectively [19]. Our current data also illustrated that the diagnostic value of the index AFP/(ALT × AST) ratio was superior to that of serum AFP marker for detecting HCC, especially in patients with elevated serum ALT level.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that serum alanine transaminase (ALT) level was signi cantly associated with elevated AFP in patients without HCC [15][16][17][18]. A recent study illustrated that the diagnostic performance of the novel index AFP/[ALT × Aspartate aminotransferase(AST)] was superior to that of AFP for HCC [19]. Hence, we hypothesize that increased ALT level might impair the diagnostic accuracy of AFP for the detection of HCC.…”
Section: Introductionmentioning
confidence: 91%
“…In the present study, we also compared the diagnostic value of the AFP marker and AFP/(ALT × AST) ratio in diagnosing HCC. Liu et al first used this novel index AFP/(ALT × AST) ratio in their study and found that the diagnostic value of the AFP/(ALT × AST) ratio was significantly better than that of AFP, with AUC up to 0.853 (95% CI 0.818–0.887) and 0.825 (95% CI 0.782–0.868) for differentiating HCC from non-HCC patients and from cirrhosis patients, respectively [ 19 ]. In the total cohort of our study, our data showed that the sensitivity of the AFP/(ALT × AST) ratio is not superior to that of AFP alone in the prediction of HCC with its AUC slightly improved.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the serum alanine transaminase (ALT) level was significantly associated with elevated AFP in patients without HCC [ 15 18 ]. A recent study illustrated that the diagnostic performance of the novel index AFP/[ALT × aspartate aminotransferase(AST)] was superior to that of AFP for HCC [ 19 ]. Hence, we hypothesize that increased ALT levels might impair the diagnostic accuracy of AFP for the detection of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…AFP can correlate with alanine aminotransferase (ALT) and aspartate aminotransferase (AST), especially in patients with hepatitis C, which implies reduced specificity of this biomarker (79). However, Liu et al have studied whether the relationship between AFP, AST and ALT could result in an index that would be useful in HCC and, despite the limitations of the research, this relationship was able to provide information regarding the diagnosis, therapeutic outcome and prognosis of HCC (80). AFP cut-off values vary according to guidelines around the world (81).…”
Section: Phasementioning
confidence: 99%